Hydro-alcoholic extract of Ochradenus baccatus exhibits anti-oxidative and anti-inflammatory properties and inhibits enzyme of uric acid metabolism: Implications for bioactive molecules - Fahad Ullah, Mohammad (Emirates Journal of Food and Agriculture, 2023)
Traditional medicines have been an accessible, affordable, and culturally acceptable model of healthcare that is trusted across the globe in terms of disease management, symptoms relief and patient satisfaction. The natural products derived from plant sources are the fundamental ingredients of traditional and folk medicine and serve as lead compounds or pharmacophore for most effective drugs in modern pharmacology for treatment of infectious and chronic diseases. Ochradenus baccatus, which belongs to family Resedaceae, is a perennial shrub, widely distributed in the arid regions of Arabian Peninsula and finds mention in the traditional medicine for reproductive health, inflammation and infection. Results: As a proof-of-concept, this study has investigated the various bioactive properties of the plant vis-à-vis anti-oxidative, anti-inflammatory and inhibition of xanthine oxidase using standard in vitro experimental models. The bioactive molecules found in the extract included flavonoids, phenolics, tannins, saponins and alkaloids in varying quantities, which are known to be associated with a multitude of pharmacological properties. Our results show that the extract caused a progressive inhibition of DPPH radical and neutralizes superoxide anions in a dose-dependent manner. The extract demonstrated its redox-active potential by means of its ability to reduce Cu (II) to Cu (I) that is detected using bathocuproine, a Cu (I)-specific sequestering agent. Progressive doses of the extracts inhibited the denaturation of protein (a factor associated with inflammation), with maximum inhibition of 70.6% observed at concentration of 600 μg/ml, after which the effect plateaued for further doses. Moreover, the extract displayed a progressive inhibitory property against the enzymatic activity of xanthine oxidase with a maximum inhibition of 66% observed at a dose of 300 μg/ml. Conclusion: Inhibition of xanthine oxidase reduces the hyperuricemia in patients with gout and nephrolithiasis as it alleviates the tendency of salt accumulation in the joints and kidney. The interest in the natural products pharmacology is escalating and exploring novel bioactive properties in plants of interest is a significant stride from the traditional knowledge to evidence-based practice